Releasing the Inner Artist: Approaching Activities Programming in Long Term Care from a Creative Arts Therapies Perspective - Sigman, Kathryn L (My University, 2018)
Residents in long term care facilities still suffer from a poor quality of life, despite the passage of legislation and recent efforts of culture change to make improvements. Engagement in the creative process may be the key to improvement. Research emphasizes the positive impacts creativity can have on well-being in the later years of life. The focus of creative arts therapies is on the facilitation of the creative process. These therapies can therefore serve as a model for activities directors, in order to create programming that focuses on the creative process and harnesses the benefits of creative activity. Programming that utilizes the creative arts therapies model will emphasize the following aspects of creativity: mastery, identity, connection, and meaning-making. Programming in long term care should also include the following components of creative arts therapies to ensure emphasis on the creative process: safe space, group cohesion, ritualized structure, and adaptability. This analysis explores how quality of life in long term care facilities can be improved by approaching activities programming from a creative arts therapies perspective. My personal position and challenges to incorporating this model are also discussed.
Citation: Sigman, K.L. (2015). Releasing the Inner Artist: Approaching Activities Programming in Long Term Care from a Creative Arts Therapies Perspective. (Unpublished masters report). Kansas State University, Kansas.